2001
DOI: 10.1128/mcb.21.4.1360-1369.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Polycomb Group Protein EED Interacts with YY1, and Both Proteins Induce Neural Tissue in XenopusEmbryos

Abstract: Polycomb group (PcG) proteins form multimeric protein complexes which are involved in the heritable stable repression of genes. Previously, we identified two distinct human PcG protein complexes. The EED-EZH protein complex contains the EED and EZH2 PcG proteins, and the HPC-HPH PcG complex contains the HPC, HPH, BMI1, and RING1 PcG proteins. Here we show that YY1, a homolog of the Drosophila PcG protein pleiohomeotic (Pho), interacts specificially with the human PcG protein EED but not with proteins of the HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 46 publications
7
119
1
Order By: Relevance
“…The Snail, but not Yin-Yang (YY) 1, contributes to the recruitment of EZH2 and HDAC1/2 to the promoter of E-cadherin Recently, evidence has been reported that the mammalian protein YY1 may contribute to the process of PRC2 recruitment to the promoter region of different target genes (Satijn et al, 2001;Schwartz and Pirrotta, 2007;Simon and Kingston, 2009), and that YY1 is needed for H3k27 methylation of target genes in muscle cells (Caretti et al, 2004). Thus, we proposed that besides Snail, YY1 may also participate in the recruitment of EZH2, to the E-cadherin promoter.…”
Section: Hdac1/2-mediated Ezh2 and Snail Interaction In Npc Cellsmentioning
confidence: 99%
“…The Snail, but not Yin-Yang (YY) 1, contributes to the recruitment of EZH2 and HDAC1/2 to the promoter of E-cadherin Recently, evidence has been reported that the mammalian protein YY1 may contribute to the process of PRC2 recruitment to the promoter region of different target genes (Satijn et al, 2001;Schwartz and Pirrotta, 2007;Simon and Kingston, 2009), and that YY1 is needed for H3k27 methylation of target genes in muscle cells (Caretti et al, 2004). Thus, we proposed that besides Snail, YY1 may also participate in the recruitment of EZH2, to the E-cadherin promoter.…”
Section: Hdac1/2-mediated Ezh2 and Snail Interaction In Npc Cellsmentioning
confidence: 99%
“…EZH2 and EED, together with YY1 (mammalian homologue of Drosophila pleiohomiotic), form a complex with histone deacetylases (HDACs) 1 and 2 that has the potential to mediate transcriptional repression 51 . It is significant that loss of function of any of the three Pc-G genes results in very early embryonic lethality 50,52,53 .…”
Section: Genomic Reprogramming In the Zygotementioning
confidence: 99%
“…The Eed/Ezh2 complex interacts through Eed with another PcG protein, Yy1, which has DNA-binding ability 25 . One possible explanation for the specificity of genes that show LOI in Eed -/-embryos could be that Yy1 targets the Eed/Ezh2 complex to specific recognition sites of imprinted genes, resulting in local histone modifications.…”
Section: These Data Identify Eed As a Member Of A New Class Of Trans-mentioning
confidence: 99%